Analysis of the Current Situation of Supply and Demand of Preschool Physical Education Talents and Research on Development Strategies - Shen , Jing (Journal of Theory and Practice of Contemporary Education, 2023)
This article analyzes and studies the current social supply and demand situation of preschool physical education talents in the new era, and uses methods such as literature review and expert interviews to propose response strategies that are conducive to the balanced development of preschool physical education talents' supply and demand, in order to promote the healthy development of preschool physical education. After investigation and analysis, it was found that the current situation of supply and demand for preschool physical education talents is mainly manifested as: the supply side and demand side do not match in quantity, gender, education, and major, the supply side has a low output of training, more women and less men, generally lower education, and a single professional direction. With the implementation of the "double reduction" policy, the total demand for early childhood physical education talents has significantly increased, male teachers are scarce, there is a large demand for highly educated talents, and there is a diversified demand for professional directions. The response strategies for the current supply and demand situation of preschool physical education talents mainly include optimizing the quantity, gender, education level, and professional structure of preschool physical education talents, increasing the quantity and scale of preschool physical education talent cultivation, male proportion, improving treatment, expanding the scale of high-level talent cultivation, and diversified professional directions.